STRUKTUR PASAR BUAH SRIKAYA DI PASAR BLUTO SUMENEP - Hopid, Hopid; Santosa, Ribut; Wahyuni, Purwati Ratna; Hamzah, Amir; Rahman, Sindi Arista (Universitas Galuh, 2023)
The exotic fruit that became the pride of farmers as an additional family income in Tanah Merah and Langsar villages is a srikaya fruit that is in great demand by Madurese people and outside the region because the texture, taste, and aroma are better than other regional production. To be able to get into the hands of consumers, marketing srikaya fruit requires marketing agencies (intermediary traders) that play a role in selling to consumers. Competition often occurs between traders especially when there is an increase in demand. This study aims to determine the market structure of srikaya fruit in Bluto Seasonal Fruit Market. Primary data were obtained through observation and interviews with traders as many as 19 respondents and literature studies were used to obtain secondary data. The data analysis method uses market share analysis, market concentration, and minimum efficiency scale (MES). The results showed that the market structure of the srikaya fruit formed in the Bluto Market from the calculation of CR4 amounted to 28.52%, which led to a monopolistic market. The barriers to entry for new traders are fairly easy to know through the MES calculation results of 8.3% with this value new traders can still compete in the fight for market share.